Penerapan Gaya Penyutradaraan Dengan Penguatan Tokoh Menggunakan Pendekatan Reaslisme Dalam Film Genius Dari Syurga - Witri Amanda; Dani Manesah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The film Genius From Heaven tells the story of a child, he is depicted as very depressed about the conflict he is currently facing. The role of a father in children with autism who can educate the public. It is hoped that this process will provide education to the public about autism sufferers, especially regarding their care. Autism sufferers also have various unique characters and sometimes their emotions often change. With a realist approach, it is hoped that this film can depict in real terms the process and struggle experienced by the main character to prove that he has other abilities that his father did not know at all.